Fostering Play-Based Learning in Early Childhood Education through Leadership and Parental Engagement - Manokaran, Archerna (Auckland University of Technology, 2025)
“Let no one ever come to you without leaving better and happier. Be the living expression of God's kindness: kindness in your face, kindness in your eyes, kindness in your smile.” ― Mother Teresa This dissertation explores ways in which early childhood education (ECE) leaders interact with parents to facilitate learning through play. It analyses the relationship between leadership practices, expectations of parents, and cultural perceptions of education (Huang, 2013; Lightfoot & Frost, 2015; Zhang & Yu, 2016). This is achieved by employing a systematic literature review as the methodology. The review is informed by established guidelines for analysis of research literature as well as the PRISMA guidelines for open data collection of literature (Booth et al., 2012; Liberati et al., 2009; Mutch, 2013; Snyder, 2019). The findings illustrate that although play-based learning is widely acknowledged as a basis for holistic development, numerous parents still doubt its value, especially those from societies that place a high priority on formal academic accomplishment (Huang, 2013). Play is an essential component of education, particularly in early childhood settings. Play-based learning allows children to develop useful information and abilities by reorienting the teaching process from a teacher-centred to a student-centred approach (Khalil et al., 2022). Play-based learning has a substantial impact on children's development in early childhood as well as their advancement in later formal education (Khalil et al., 2022). Vygotsky's sociocultural theory views play as a key activity that fosters emotional, cognitive, and social development by allowing children to experiment with imagined elements and self-directed norms (Vygotsky, 1976). Joy is evident and frequently connected to early childhood environments and children's play. Even if joy is acknowledged and validated, barriers including administrative duties, regulations, expectations from parents, burnout, and time constraints can prevent educators from fully embracing joyful, play-based pedagogies (Little & Karaolis, 2023). Some of these barriers may be caused in part by parents' lack of support for their children's play, which is fuelled by high standards and demands for academic success as well as a lack of knowledge about the value of play in children's development (Karuppiah, 2022). Early childhood education leaders are under more pressure to bridge understanding through relational, honest, and culturally sensitive communication because of this tension (Lindsay, 2024; Heikkinen et al., 2024). This dissertation makes an argument that effective early childhood education leadership is a relational and ethical practice based on Te Whāriki (Ministry of Education, 2017) values rather than just a collection of administrative skills. Te Whāriki (Ministry of Education, 2017), the early childhood curriculum of New Zealand, has a strong emphasis on connections, family and community, empowerment, and holistic development as key pillars that enable inclusive and culturally sensitive pedagogies. It is crucial to respect the various realities and goals of early learning communities by acknowledging Te Whāriki as an intellectual framework (Ministry of Education, 2017). Therefore, this dissertation suggests curriculum initiatives that position families as co- weavers of education alongside educators and children, equity-driven funding, and ongoing professional development (Ministry of Education, 2018; Wood & Hedges, 2024). A personal reflection on my experiences working as an early childhood educator is included in the final chapter, which also highlights the continuous battle for respect and recognition in the field of early childhood education. It calls for a continued commitment to diversity and respect in early childhood education and ends with a message of empowerment for early childhood education professionals, reinforcing the critical role they play (Ballaschk et al., 2024; Cooper, 2025; OECD, 2019). Mother Teresa's words align well with Te Whāriki's (Ministry of Education, 2017) objective for relationships that respect and uphold the mana of all tamariki and whānau serves as the foundation for this dissertation.